DAMPAK PENGUMUMAN LAPORAN KEUANGAN TERHADAP KEGIATAN PERDAGANGAN SAHAM DAN VARIABILITAS TINGKAT KEUNTUNGAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
This paper investigates the impact of financial statements of trading activities on stock volume and return variabilities. In general we found that there is an increase in trading activities in the period in which financial statements are published. Trading activities in this period are higher than trading activities in other periods. There is a significant difference between trading activities for December financial statements (audited) and trading activities for March financial statements (unaudited). We conclude that formalization of accounts has some values, despite lower recognition of public accounts and financial statements. We also found somewhat dissappointing results for the impact of financial statements on return variability. In general there are no differences in return variability before and after the publication of financial statements, and there aren't significant differences between return variability during period in which the financial statements are announced and other periods. We found a significant difference in return variability before and after the publication of March financial statements, but no differences between the December and March financial statements. These results lead us to conclude that March financial statements convey new information a higher return variability before the financial statements are published than after. .We also conclude that December financial statements do not convey new information because they represent only a confirmation of the interim reports. If December financial statements showed some adjusments (possibly negative) on the interim reports, significant differences between return variability in December and March could be expected.